1997
DOI: 10.1152/ajpcell.1997.272.6.c1804
|View full text |Cite
|
Sign up to set email alerts
|

Volume regulation in NIH/3T3 cells not expressing P-glycoprotein. II. Chloride and amino acid fluxes

Abstract: The osmolyte function of amino acids and Cl in native NIH/3T3 cells not expressing the P-glycoprotein was examined by investigating the free amino acid concentration and the swelling-activated efflux of [3H]taurine, as representative of amino acids, and of 125I, as a tracer for Cl. Taurine and 125I efflux was activated by 20 and 30% hyposmotic solutions. At 50% hyposmotic solutions, the osmolyte pool was essentially depleted. The Cl channel blockers 5-nitro-2-(3-phenylpropyl-amino)benzoic acid, 1,9-dideoxyfors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…59, 61) and NIH3T3 fibroblasts (0.025-0.055 mol/mg protein; Refs. 42,63). With the use of average values for cellular water and protein content, i.e., 3.24 ml cell water/g cell dry wt (18) and 0.78 g protein/g cell dry wt (15), the taurine content in A2780 cells corresponds to a cellular taurine concentration at 4.5 Ϯ 0.7 mM.…”
Section: Resultsmentioning
confidence: 99%
“…59, 61) and NIH3T3 fibroblasts (0.025-0.055 mol/mg protein; Refs. 42,63). With the use of average values for cellular water and protein content, i.e., 3.24 ml cell water/g cell dry wt (18) and 0.78 g protein/g cell dry wt (15), the taurine content in A2780 cells corresponds to a cellular taurine concentration at 4.5 Ϯ 0.7 mM.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32] We had observed that ddFSK was able to block late apoptotic events. 24 Here we explain those data through the definition of a novel activity of ddFSK as a cell energy metabolism blocker.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the great majority of the taurine and Cl Ϫ efflux are mediated by separate channels and that the taurine channel is different from VRAC. Further support for this view is that: 1) swelling-induced taurine release in the absence of Cl Ϫ channel activity has been demonstrated in Xenopus oocytes (947) and in mammary tissue explants (924); 2) the taurine and anion efflux pathways differ with respect to their time course of activity following hypotonic exposure (672,773,961), 3) the two pathways have different sensitivity towards DIDS and arachidonic acid (192,499,672) (for EAT cells see Table 6), and 4) regulation by RhoA (786). It is noted that, in fact, the taurine leak pathway accounts for 5% of the total g Cl in EAT cells (50% reduction in osmolarity; Ref.…”
Section: Molecular Identity Of the Taurine Efflux Pathwaymentioning
confidence: 95%
“…Released arachidonic acid is in itself a bioactive lipid, which can directly activate transport pathways for, e.g., K ϩ (450, 749) and organic osmolytes (491,868). In contrast, at higher concentrations, arachidonic acid directly inhibits swelling-activated K ϩ , Cl Ϫ , and taurine efflux (316, 489,672,881). Arachidonic acid is also an important regulator of cellular signaling processes.…”
Section: Plamentioning
confidence: 99%